Values and beliefs that shape cattle breeding in southwestern Burkina Faso - Zoma‑Traoré, B.; Ouédraogo-Koné, S.; Soudré, A.; Ouédraogo, D.; Yougbaré, B.; Traoré, A.; Khayatzadeh, N.; Mészáros, Gábor; Burger, P.A.; Okeyo Mwai, Ally; Sölkner, J.; Wurzinger, Maria; et al. (Springer, 2021)
Cattle production in southwestern Burkina Faso is under pressure because of resource scarcity, changing climate, and cattle diseases. Well-adapted local breeds, such as Lobi taurine cattle, are increasingly replaced by more productive exotic breeds. Community-based breeding programs (CBBPs) could be a viable option for preserving the breed and improving its productivity. Presuming that CBBPs would succeed only if they align with producers’ beliefs and values, we relied on a combination of conceptual frameworks (theory of basic values, rural livelihood transitions) to explore the values and beliefs of cattle producers. Security was the respondents’ dominant value in their aim to mitigate threats to livelihood, and it was closely linked to achievement in terms of harvest and animal quantity. Livestock-oriented respondents particularly valued conformity with accepted social roles, while achievement and power were more pronounced among crop-oriented respondents. We conclude that CBBPs, to be successful, will need to reduce threats to participants’ livelihood and make benefits of participation immediately visible. We consider the emergence of trusted leadership from the community to be pivotal for creating momentum for novel arrangements in cattle keeping and feeding.